A Complex Case of Sacral Herpes Zoster Complicated by a Vulvar Abscess Unmasking Uncontrolled Type 2 Diabetes Mellitus - Nova Faisal Waber; Faradiani Rasyidi (The International Journal of Medical Science and Health Research, 2025)
Introduction: Genital herpes zoster (HZ), a reactivation of the latent Varicella-Zoster Virus (VZV), is an uncommon clinical entity, as the sacral dermatomes are infrequently affected. The severity and clinical course of HZ can be profoundly influenced by underlying conditions that impair cell-mediated immunity, such as diabetes mellitus (DM). Case Illustration: We present the case of a 60-year-old female who presented to the emergency department with a two-day history of an acute, severely painful, unilateral vesicular eruption in the sacral dermatome, consistent with HZ. Her condition was complicated by the rapid development of a large, fluctuant vulvar abscess. Crucially, initial laboratory investigations revealed severe hyperglycemia with a random blood sugar of 306 mg/dL, leading to a new diagnosis of Type 2 Diabetes Mellitus (T2DM). Discussion: The patient's management necessitated a coordinated, multidisciplinary approach. This involved high-dose oral antiviral therapy to control VZV replication, urgent surgical incision and drainage of the vulvar abscess for source control, broad-spectrum systemic antibiotics to treat secondary bacterial infection and sepsis, and aggressive glycemic control with a multi-dose insulin regimen. This report delves into the intricate pathophysiological triad where the impaired immunity of undiagnosed diabetes precipitated VZV reactivation, the acute viral infection triggered severe metabolic decompensation, and the resultant state of acute hyperglycemia and immune paralysis created a permissive environment for a life-threatening bacterial superinfection and abscess formation. Conclusion: This case underscores the critical importance of including HZ in the differential diagnosis of acute, unilateral ulcerative genital lesions. Furthermore, it highlights how a severe or complicated HZ presentation can be the initial clinical manifestation of previously undiagnosed and uncontrolled T2DM, mandating prompt investigation for underlying metabolic disorders. The successful outcome demonstrates the necessity of an integrated multidisciplinary strategy in managing such complex clinical emergencies.